Net Irrigation Requirements for Florida Turfgrass Lawns: Part 2 - Reference Evapotranspiration Calculation - Consuelo C. Romero; Michael D. Dukes (EDIS)
Urban water users need specific recommendations to irrigate efficiently and for planning and regulatory programs. As the second step in the process of estimating net irrigation requirements. This 9-page fact sheet calculates reference ET for ten locations in Florida and one in Alabama. Written by Consuelo C. Romero and Michael D. Dukes and published by the UF Department of Agricultural and Biological Engineering, August 2011. (Image from ca.gov)